Effects of Drip Irrigation and Cultivation Methods on Establishment of Seeded Tall Fescue - Alex P. Bach; Dale J. Bremer; Cathie C. Lavis; Steven J. Keeley; Mu Hong (Kansas Agricultural Experiment Station Research Reports, 2022)
Subsurface drip irrigation (SDI) is becoming increasingly popular for maintaining turfgrass, in part because it conserves water. However, turf managers considering SDI may wonder if SDI is effective in establishing seeded turfgrass, should the need arise. Also, can verticutting or core aeration be used to establish the seedbed without damaging the buried driplines? Is one of those two cultivation methods better than the other? These questions were evaluated in this study. An aboveground drip irrigation system (AGD) was also evaluated because it has been suggested as a portable method for establishing turfgrass planted along roadsides. Results indicated seeded tall fescue [Schedonorus arundinaceus(Schreb.) Dumort.] turf was successfully established with SDI in fine-textured soil in a transition zone climate. Seeded turf established faster with SDI than AGD or overhead sprinkler irrigation. With SDI, establishment was faster when water was applied 2× than 3× or 1× per day (the same amount of water per day was applied in each, but was split into one, two, or three applications). Core aerification and verticutting for seedbed preparation were equally successful in establishing seeded tall fescue using SDI. Buried driplines were not damaged under the conditions of this study, but depths of cultivation and driplines must always be considered to avoid SDI damage.
Keywords: subsurface drip irrigation; sprinkler irrigation; turfgrass establishment; seedbed cultivation